The COVID-19 Crisis as a Teachable Moment for Lifestyle Change in Dutch Cardiovascular Disease Patients - Brust, Michelle; Gebhardt, Winifred A.; Numans, Mattijs E.; Kiefte-de Jong, Jessica C. (Frontiers in Psychology, 2021)
Objective: When lifestyle changes are needed, life events or crises such as COVID-19 may function as ‘teachable moments’. This study aimed to explore whether the pandemic can provoke a teachable moment regarding lifestyle change in cardiovascular disease patients. Method: In this cross-sectional survey study, 830 cardiovascular disease patients reported their intentions to change lifestyle, instigated by the corona crisis, together with risk perception, affective impact, and changed self-concept, based on a ‘teachable moments’ framework. Results: Between 8-28% of the sample reported increased intentions to optimize lifestyle behaviors, particularly related to general lifestyle (28%), physical activity (25%), and diet (21%). Multivariate regression analyses revealed that changed self-concept was associated with higher intentions to improve general lifestyle (B= 0.26; CI = 0.19 - 0.33), physical activity (B = 0.23; CI = 0.16 - 0.30), and smoking (B = 0.29; CI = 0.01 – 0.57). In addition, changed self-concept and affective impact were both significantly associated with higher intentions to improve diet (resp. B = 0.29; CI = 0.21 - 0.36 and B = 0.12; CI = 0.04 – 0.21) and to limit alcohol consumption (resp. B = 0.22; CI = 0.13 - 0.30 and B = 0.11; CI = 0.01 - 0.20). We did not find evidence for an important role of risk perception on behavior change intentions. Conclusion: The COVID-19 crisis evoked a potential teachable moment for lifestyle change in cardiovascular disease patients, driven by a change in a patient’s self-concept and to a lesser extent by an affective impact of the COVID-19 crisis. These results suggest an important window of opportunity for healthcare professionals to utilize the pandemic to promote a healthy lifestyle to their patients.